Immersion and Gameplay Experience: A Contingency Framework. (2nd December 2010) - Örtqvist, Daniel; Liljedahl, Mats
Abstract : The nature of the relationship between immersion and gameplay experience is investigated, focusing primarily on the literature related to flow. In particular, this paper proposes that immersion and gameplay experience are conceptually different, but empirically positively related through mechanisms related to flow. Furthermore, this study examines gamers' characteristics to determine the influence between immersion and gameplay experiences. The study involves 48 observations in one game setting. Regression analyses including tests for moderation and simple slope analysis are used to reveal gamers' age, experience, and understanding of the game, which moderate the relationship between immersion and gameplay experience. The results suggest that immersion is more positive for gameplay experience when the gamer lacks experience and understanding of the game as well as when the gamer is relatively older. Implications and recommendations for future research are discussed at length in the paper.